Pengelolaan Supervisi Akademik Sekolah Dasar Islam Terpadu Ash-Haabul Kahfi Lubuk Alung - Asnita Putri Dewi (Universitas Kristen Satya Wacana, 2020)
This study aims to determine how the management of academic supervision at the Ash-Haabul Kahfi Lubuk Alung Integrated Islamic Elementary School in improving teachers competency and professionalism. The research approach was conducted qualitatively with descriptive methods. Data collected through observation, interviews, and documentation. The results of the study are: (1) In conducting academic supervision planning activities, the school principal had implemented it well. The school principal and teachers had compiled a one-year program design through the school meeting forum. (2) In the process of conducting academic supervision, the principal is considered to have no understanding of academic supervision, because it only focuses on teacher administration examination only (3) Follow-up academic supervision has not been maximized run by the principal as a supervisor, because only fostering teachers whose administration are incomplete. The lack of guidance for school principals related to the learning process, teacher skills in teaching, makes teachers not experience a significant increase in terms of competence and profession as a teacher.